Dampak Pariwisata terhadap Sosial Subak dan Perbandingan Pendapatan Rumah Tangga Petani pada Sektor Pertanian dan Sektor Pariwisata (Studi Kasus di Subak Teges, Desa Peliatan, Kecamatan Ubud, Kabupaten Gianyar) - ARTINI, KADEK SOMA YULIANA; AMBARAWATI, IGAA; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
The Social Impact of Tourism on Subak and Comparison of Farmers' Household Income in the Agricultural Sector and the Tourism Sector (Case Study in Subak Teges, Peliatan Village, Ubud District, Gianyar Regency) Tourism is a sector that significantly contributes to the economic growth of Bali Province. The development of tourism will also develop other related sectors, such as agriculture, livestock, plantation and handicraft. Farmers in Subak Teges, Peliatan Village, Ubud District, Gianyar Regency for instance, have experienced the economic benefits generated by tourism development. This study aims to see the impact of tourism on subak, particularly the function of subak, as well as to compare the farmer households’ income from the agricultural and the tourism sectors. The sampling technique used was purposive random sampling involving 41 respondents. The data was analyzed quantitatively and qualitatively. The study results show that tourism provides significant changes to the five functions of subak. The household income of farmers working in the agricultural sector and the tourism sector differs significantly (t-test shows a significance of 0.000). The average household income of farmers in the agricultural sector is only Rp. 1,282,635 per month, while in the tourism sector it is Rp. 3,113,415 per month. The annual farmer households income in the agricultural sector is Rp. 15,391,623, while in the tourism sector it is Rp. 37,360,976. For that reason, it is important for Subak Teges to maintain the synergy between agriculture and tourism by promoting Subak as a tourism destination and preserving rice fields.